DSTORM‐Based Single‐Cell Protein Quantitative Analysis Can Effectively Evaluate the Degradation Ability of PROTACs. (24th January 2023) - Yang, Fuwei; Tan, Yuxin; Wu, Cheng; Xin, Lilan; Huang, Zhenli; Zhou, Haibing; Zhou, Fuling
Abstract: As an emerging therapeutic strategy, proteolysis‐targeting chimeras (PROTACs) have been proven to be superior to traditional drugs in many aspects. However, due to their unique mechanism of action, existing methods for evaluating the degradation still have many limitations, which seriously restricts the development of PROTACs. In this methodological study, using direct stochastic optical reconstruction microscopy (dSTORM)‐based single‐cell protein quantitative analysis, we systematically investigated the dynamic degradation characteristics of FLT3 protein during PROTACs treatment. We found that the distribution of FLT3 varies between FLT3‐ITD mutation and FLT3‐WT cells. PROTACs had an obvious time‐course effect on protein degradation and present two distinct phases; this provided a basis for deciding when to evaluate protein degradation. High concentrations of PROTACs were more effective than long‐time administration because a higher D max was achieved. Two‐color dSTORM‐based colocalization analysis efficiently detected the proportion of ternary complexes, making it very useful in screening PROTACs. Taken together, our findings show that the dSTORM method is an ideal tool for evaluating PROTACs and will accelerate the development of new PROTACs. Abstract : Detecting density dynamics : By using innovative single‐color and two‐color direct stochastic optical reconstruction microscopy, we have developed a simple and visual method that could analyze dynamic density changes in proteins of interest after treatment with PROTACs, at the single‐cell level and in a fully quantitative degree. This method will be useful in screening PROTACs and accelerating the development of new PROTACs.